Model Kepemimpinan Situasional Hersey, Blanchard, dan Nicholls dalam Perspektif Kepemimpinan Pendidikan Islam - Fatimatul Baroroh; Sulalatun Nikma (Journal of Islamic Education, 2026)
: Leadership is a critical factor in determining the success of educational institutions, including within the context of Islamic education. The increasingly dynamic changes in the educational environment require leaders of educational institutions to possess the adaptability to adjust their leadership styles to the organizational conditions and characteristics of the human resources under their leadership. One relevant approach to addressing these challenges is the situational leadership model developed by Paul Hersey and Ken Blanchard and refined by Nicholls. This study aims to analyze Hersey and Blanchard’s situational leadership concept, the level of follower readiness, the leadership styles derived from this model, and its relevance from the perspective of Islamic educational leadership. The research method employed is a literature review (library research) involving the examination of various relevant scientific literature, including books and journal articles. Data analysis was conducted using a descriptive qualitative approach through the process of collecting, selecting, and interpreting literature sources related to situational leadership theory and Islamic educational leadership. The results of the study indicate that the situational leadership model emphasizes the importance of alignment between leadership styles and the level of follower readiness in carrying out specific tasks. The level of followers’ readiness is classified into four categories—low to high—which determine the application of the telling, selling, participating, and delegating leadership styles. This approach provides flexibility for leaders to adjust directive and supportive behaviors according to organizational conditions and members’ needs. From an Islamic education perspective, the situational leadership model aligns with leadership values such as trustworthiness, responsibility, justice, and consultation. The integration of situational leadership theory with Islamic leadership values is expected to create an adaptive, humanistic, and effective leadership model that enhances the quality of management and the performance of Islamic educational institutions.